Identification of Marker Peptides in Gelatins from Sika Deer (Cervus nippon) Using Ultra-High-Performance Liquid Chromatography–Quadrupole-Exactive-Orbitrap Mass Spectrometry - Kouharu Otsuki; Aya Nomizo; Mi Zhang; Dongxia Li; Takashi Kikuchi; Wei Li (Molecules)
Gelatin from deer has garnered attention as a high-value health-promoting resource given its history of usage as a traditional Chinese medicine and recent studies demonstrating its biological activities. Mass spectrometry-based methods have increasingly been employed for species identification in collagen-based materials, effectively addressing challenges in quality control and authenticity verification. This study aims to identify characteristic marker peptides in gelatins from sika deer (Cervus nippon) to support their effective use as a health-promoting resource. Gelatin samples were enzymatically digested, and the resulting peptide mixtures were analyzed using ultra-high-performance liquid chromatography coupled with quadrupole Q-Exactive-Orbitrap mass spectrometry (UHPLC-Q-Exactive-Orbitrap MS). Marker peptide candidates were selected based on their high detection intensity and a literature review. Among the 28 selected marker peptide candidates, four peptides (P11, R2, R3, and R4) were defined as characteristic of sika deer gelatin. Comparative analyses with gelatins derived from donkey hide, bovine, porcine, and fish samples further confirmed the specificity of these peptides. These findings establish a robust analytical method for verifying the authenticity of sika deer gelatin, contributing to its safe and effective use as a health-promoting resource.